I Can Move - Suhr, Mandy; Gordon, Mike (Minneapolis : Carolrhoda Books, 1992)
Explains how our bones and muscles help our body move.
Keywords: Musculoskeletal system -- Juvenile literature; Skeleton; Bones; Muscles